2011
DOI: 10.1111/j.1475-6773.2011.01288.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Hospital Costs, Payments, and Profitabilty for Cardiac Valve Replacement Surgery

Abstract: Objective. Examine the variation for Medicare and privately insured patients in hospital costs, payments, and contribution margins and their association with characteristics of the patients, hospitals, and hospital markets. Data Sources. Administrative records for 1,858 patients undergoing cardiac valve replacement surgery were obtained from 37 hospitals in 7 states for 2008. Study Design. Bivariate and multivariate statistical analyses of costs, payments, and profitability (contribution margin) for Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…This method captures actual costs (not charges), thereby avoiding issues with estimating cost‐to‐charge ratios that are dependent on treatment facility and payer. These methods have been widely applied in health economics assessments for cardiovascular procedures and for AF ablation specifically . We defined ablations as outpatient only if all associated reimbursements were classified as outpatient (“23‐hour stay”) and defined ablations as inpatient if any associated reimbursements were classified as inpatient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method captures actual costs (not charges), thereby avoiding issues with estimating cost‐to‐charge ratios that are dependent on treatment facility and payer. These methods have been widely applied in health economics assessments for cardiovascular procedures and for AF ablation specifically . We defined ablations as outpatient only if all associated reimbursements were classified as outpatient (“23‐hour stay”) and defined ablations as inpatient if any associated reimbursements were classified as inpatient.…”
Section: Methodsmentioning
confidence: 99%
“…These methods have been widely applied in health economics assessments for cardiovascular procedures and for AF ablation specifically. [10][11][12][13] We defined ablations as outpatient only if all associated reimbursements were classified as outpatient ("23-hour stay") and defined ablations as inpatient if any associated reimbursements were classified as inpatient. We accounted for inflation by normalizing all dollars to October 2014 using the Medical Care Consumer Price Index.…”
Section: Methodsmentioning
confidence: 99%
“…Medicare, regulated and funded by the US government, provides insurance coverage for aged (65 years old or older) and disabled persons. Studies have suggested that Medicare generally has a lower reimbursement rate than commercial plans for the same procedure or service 13,14. Because health care costs are the main study outcome, separate analyses on commercially insured and Medicare patients minimize the bias introduced by these different payment rates.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, economic evaluations undertaken in North America will need to draw upon data from the public, private and not-for-profit sectors. For example, in the USA the physician fee component of cost can be obtained from Medicare (CMS 2014 ); however, hospital, test and pharmaceutical costs will often need to be obtained separately and frequently vary according to provider and indeed the payer (Robinson 2011 ). In the USA, Medicare provides increasingly detailed information on costs they incur for a wide range of services (CMS 2012 ).…”
Section: Finding Evidence On Resource Use and Costsmentioning
confidence: 98%